Inmate violence and correctional staff burnout: the role of sense of security, gender, and job characteristics - Isenhardt, Anna (Journal of interpersonal violence, 2020)
Violence in the workplace has serious consequences for employees and organizations. Based on a survey in early 2012 among employees from all work areas of 89 of the total 112 correctional facilities in Switzerland resulting in a sample of 2,045 employees (response rate 48.5%), this study (a) analyzed whether victimization has an impact on correctional staff burnout, (b) tested the hypothetical mediating role of sense of security in the relationship between victimization and burnout, and (c) included gender and job characteristics because work experiences and exposure to violence of staff differ strongly with gender and work tasks. Two different forms of violence were considered: (a) experienced violence (inmates-on-staff) and (b) observed violence (inmate-on-inmate). Analysis was carried out using structural equation modeling. Results show that victimization and witnessing violence between inmates negatively affect the personal sense of security and increase correctional staff burnout. In addition, the sense of security mediated the effect from experienced and observed violence on burnout. Gender and job characteristics also proved to be important. This is especially true for staff working as correctional officers and for employees working with young inmates and with inmates awaiting trial who reported a greater exposure to violence and a lower sense of security. The study adds to the knowledge on violence and its outcomes in corrections and contributes to the literature on the consequences of workplace violence in general and, specifically, in social service occupations.